Livelihood interests, organizational discipline, and grassroots participation in Ecuadorian indigenous movement protests. Issue 1 (2nd January 2019) - Soper, Rachel
ABSTRACT: The Ecuadorian indigenous movement has received much scholarly attention for its ability to mobilize large numbers of people in its protest campaigns. These mobilizations rely on the participation of rural indigenous community members who make up the organizational base of the movement. Yet, most scholarship on the movement focuses on national-level leadership. As such, little is known about the perspectives of indigenous community members and why they do or do not participate in these protests. This article draws on ethnographic fieldwork and qualitative interviews with respondents in three rural indigenous communities in the highlands of Ecuador to see how participation varies within and between communities. I found that differing degrees of participation can be explained in part by livelihood interests and in part by organizational discipline. Certain themes cut across communities, such as being skeptical of careerism; feeling taken advantage of by movement leadership; and perceiving protest campaigns as going against the livelihood interests of those who make a living in the agro-export sector. These findings contribute to existing scholarship on the contradictions inherent within indigenous movement political discourse and alternative development ideologies more broadly.